PENGARUH WORK-FAMILY CONFLICT, KUALITAS KEHIDUPAN KERJA DAN STRES KERJA TERHADAP KINERJA PERAWAT WANITA PADA RUMAH SAKIT PERMATA HATI DURI - Manurung Yustina Icha; Taufiqurrahman Taufiqurrahman; Roesdi Rosnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research was conducted at Permata Hati Hospital Duri which is located onJenderal Sudirman Street No. 37, Duri City, Riau. The purpose of this research isto find out how the effect of work family conflict, quality of work life and workstress on the performance of female nurses at the Permata Hati Hospital Duri.The population in this research were married female nurses, totaling 60 people.The sampling technique chosen was saturated sampling or census so that theentire population was sample. Data processing was carried out using the SEMmethod with the SmartPLS version 3 application. The results of this study indicatethat: 1) Work family conflict has a negative and significant effect on theperformance of female nurses at Permata Hati Duri Hospital, 2) Quality of worklife has a positive and significant effect on the performance of female nurses atPermata Hati Duri Hospital, 3) Work stress has a negative and significant effecton the performance of female nurses at Permata Hati Duri hospital. Keywords: Work Family Conflict, Quality of Work Life, Work Stress, NursesPerformance